2019
DOI: 10.1002/chem.201900646
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate‐Rich Biomimetic Peptides Shed Light on High‐Affinity Hyperphosphorylated Uranyl Binding Sites in Phosphoproteins

Abstract: Some phosphoproteins such as osteopontin (OPN) have been identified as high‐affinity uranyl targets. However, the binding sites required for interaction with uranyl and therefore involved in its toxicity have not been identified in the whole protein. The biomimetic approach proposed here aimed to decipher the nature of these sites and should help to understand the role of the multiple phosphorylations in UO22+ binding. Two hyperphosphorylated cyclic peptides, pS168 and pS1368 containing up to four phosphoserin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…Both acidic residues (Asp/Glu) and phosphoserines (pSer) were systematically introduced in the key positions (X1, X3, X6, and X8) of the peptide [32][33][34]. It showed that the stability of UO 2 2+ -peptide complex increased successively by replacing the 4 Glu residues (logK = 8.2) in these positions with 1-4 pSer residues, i.e., 3 Glu/1 pSer, logK = 9.2; 2 Glu/2 pSer, logK = 10.1; 1 Glu/3 pSer, logK = 10.7; and 4 pSer, logK = 11.3.…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both acidic residues (Asp/Glu) and phosphoserines (pSer) were systematically introduced in the key positions (X1, X3, X6, and X8) of the peptide [32][33][34]. It showed that the stability of UO 2 2+ -peptide complex increased successively by replacing the 4 Glu residues (logK = 8.2) in these positions with 1-4 pSer residues, i.e., 3 Glu/1 pSer, logK = 9.2; 2 Glu/2 pSer, logK = 10.1; 1 Glu/3 pSer, logK = 10.7; and 4 pSer, logK = 11.3.…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…It showed that the stability of UO 2 2+ -peptide complex increased successively by replacing the 4 Glu residues (logK = 8.2) in these positions with 1-4 pSer residues, i.e., 3 Glu/1 pSer, logK = 9.2; 2 Glu/2 pSer, logK = 10.1; 1 Glu/3 pSer, logK = 10.7; and 4 pSer, logK = 11.3. Moreover, both 1 Glu/3 pSer and 4 pSer peptides can trap two UO 2 2+ ions and form bimetallic complexes, suggesting a decisive role of the phosphate groups [34]. In an application research, Hu, Wang and co-workers designed a fluorescent sensor for detection of uranyl ions based on the cyclic peptide [35].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…19 Higher affinity was achieved by phosphorylation of the binding sites. [20][21][22][23] However, we found that high affinity can be achieved not only through phosphorylation but also by selecting an appropriate size of peptides. For example, previously studied peptide A1 (c[EREPGEWEPG]) was found to have a binding energy of À43.6 kcal mol À1 with UO 2…”
Section: Uranyl(vi) Binding To Cyclic Peptidesmentioning
confidence: 95%
“…four coordinating glutamate and/or phosphoserine (pSer) residues. [11,[17][18][19] These peptides were named pSn, n being the number of pSer and (4À n) being accordingly the number of coordinating glutamates in the sequence. Sequences of the peptides used in this study are described in the Supporting Information (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, analysis of the Trp fluorescence data had been performed making assumptions on the emitting or non-emitting character of these metal species. [17] It was thus necessary to confirm the obtained stability constants prior to building an affinity scale. NaphP fluorescence being independent from the fluorescence of the UO 2 pSn complexes, it was possible to re-assess these constants by observing Naph fluorescence (λ ex = 344 nm, λ em = 380 nm).…”
Section: Methodsmentioning
confidence: 99%